Feasibility Study on the Integration of Innovation and Entrepreneurship Education and Occupational Therapy Training Mode for College Students Based on Big Data - Yan Yang; Juan Xie (Occupational Therapy International)
With the development of information technology, the status of the traditional teaching method combining chalk and blackboard is declining. People need a novel teaching method to reform traditional education, so the hybrid teaching mode combining the advantages of both is produced and has become a major research hotspot in the field of education technology at present. Further accelerating the reform of innovation and entrepreneurship teaching in higher education institutions and improving students’ innovation and entrepreneurial ability based on big data technology are the fundamental measures to do a good job in managing college students’ entrepreneurship and employment. Therefore, the reform of dual-innovation education in colleges and universities has become a research hotspot in recent years. How to combine the two aforementioned research hotspots in order to improve college students’ dual-innovation ability is a key issue that needs to be solved urgently. College students’ innovation and entrepreneurship practice is in full swing in colleges and universities, but the success rate of college students’ entrepreneurship is not high. In order to promote the development of college students’ entrepreneurial practice, colleges and universities can give them the necessary help. Integrating the content of “dual innovation” education with big data technology into the ideological and political education of college students can not only improve the ideological and political quality and moral and psychological quality of college students but also convey the relevant legal policies of innovation and entrepreneurship to college students. Today’s society has entered the Internet era, the resource of information technology, and the rapid development of the Internet which provides good technical support and rich content choices for the innovation of ideological and political education of college students in the context of “dual innovation,” but it also poses new challenges for the ideological and political education of college students. By studying the exercise data of groups at all levels in the campus, we analyze and compare the overall exercise situation of each type of group and explore and study the overall exercise situation of various classes, grades, schools, etc., to understand the physical activity. We can build a group of ideological and political education teachers with innovative and entrepreneurial literacy based on big data analysis. Only in this way can the ideological and political education of college students really give some help to the practice of innovation and entrepreneurship of college students and stimulate the potential of innovation and entrepreneurship of college students from a deeper level.